Time-Dependent Associations Between Body Composition, Physical Activity, and Current Asthma in Women: A Marginal Structural Modeling Analysis - Bédard, Annabelle (Am J Epidemiol, 2017)
The role of obesity in adult asthma is well-known and has been partly attributed to a confounding role of physical inactivity. However, the interrelationships between obesity, physical activity, and asthma have been incompletely addressed, probably because their time-dependent and bidirectional nature represents a methodologically challenging research question. We aimed to estimate the independent causal effects of body mass index (BMI; weight (kg)/height (m)(2)) and physical activity on current asthma using marginal structural models (MSMs). MSMs were applied to 15,353 adult women from a 2011 case-control study of asthma (Asthma-E3N) nested within the French E3N study (Etude Epidémiologique auprès de Femmes de la Mutuelle Générale de l'Education Nationale). Three time periods (1997-2000-2002, 2000-2002-2005, and 2002-2005-2011) were defined, where exposures (BMI and physical activity) were measured at time t, outcome (current asthma) was measured at time t + 1, and covariates were measured at time t − 1 or at baseline. A strong significant and positive dose-response relationship between BMI and current asthma was observed (odds ratios were 0.90 (95% confidence interval (CI): 0.79, 1.03), 1.29 (95% CI: 1.17, 1.42), and 1.87 (95% CI: 1.60, 2.18) for the BMI groups <20.0, 25.0–29.9, and ≥30.0, respectively, versus the normal-weight group (BMI 20.0–24.9)). We found no association between physical activity and current asthma. Our results suggest an independent causal deleterious effect of overweight and obesity on current asthma, whereas no independent causal effect of physical activity was found.